Temporal and Spatial Expression of CCN Genes in Zebrafish - Fernando, Carol A (Wiley-Liss, Inc., 2010)
The six mammalian CCN genes (Cyr61, CTGF, Nov, WISP1, WISP2, WISP3) encode a family of secreted, cysteine-rich, multimodular proteins having roles in cell proliferation, adhesion, migration, and differentiation during embryogenesis, wound healing, and angiogenesis. We used bioinformatics to identify 9 CCN genes in zebrafish (zCCNs), 6 of which have not been previously described. When compared with mammalian CCN family members, 3 were paralogs of Cyr61, 2 of CTGF, 2 of WISP1, 1 of WISP2, and 1 of WISP3. No paralog of Nov was found. In situ hybridization was performed to characterize the sites of expression of the zCCNs during early zebrafish development. zCCNs demonstrated both unique and overlapping patterns of expression, suggesting potential division of labor between orthologous genes and providing an alternate approach to gene function studies that will complement studies in mammalian models. Developmental Dynamics 239:1755–1767, 2010. © 2010 Wiley-Liss, Inc.